2018
DOI: 10.29219/fnr.v62.1343
|View full text |Cite
|
Sign up to set email alerts
|

The associations between diet and physical activity with body composition and walking a timed distance in adults with Prader–Willi syndrome

Abstract: BackgroundResearch on aging in Prader–Willi syndrome (PWS) is limited, although people with PWS are living longer. Individuals with PWS present with high fat mass, low lean mass, and low levels of physical activity (PA). Previous reports in children and young adults with PWS show inadequate nutrient intake and body fat percentage indicating obesity. Previous studies in PWS rarely included individuals beyond young adulthood, especially studies conducted in the United States. This study includes adults from 18 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…The completed dietary record was then returned at the following visit and reviewed for completeness and portion sizes. The dietary record information was entered into FoodWorks nutrient analysis software [26] to obtain information regarding carbohydrate, protein, fat, as well as vitamin D intakes [27].…”
Section: Methodsmentioning
confidence: 99%
“…The completed dietary record was then returned at the following visit and reviewed for completeness and portion sizes. The dietary record information was entered into FoodWorks nutrient analysis software [26] to obtain information regarding carbohydrate, protein, fat, as well as vitamin D intakes [27].…”
Section: Methodsmentioning
confidence: 99%
“…However, body composition was not evaluated in the latter study, while in the Italian study the authors reported a negative correlation between 25OHD levels and fat mass in both groups, despite the youth PWS patients presenting a higher fat mass percentage than the controls. Similarly, Woods et al (2018) confirmed that there is inadequate dietary vitamin D intake in adulthood PWS, as they showed through a study of 19 PWS adults, none of whom met vitamin D recommendations from diet alone (25OHD levels were not provided) [9]. Of interest, the authors of this study showed that their PWS adults had lower body fat percentages than the percentages reported in most studies, especially in PWS adults of a younger age, likely due to earlier diagnoses and interventions in diet, exercise, and daily routines, as well as through use of rhGH replacement therapy.…”
Section: Discussionmentioning
confidence: 98%
“…The common treatments to counteracting the pathological characteristics of PWS-which include restricted caloric intake, increased physical activity, and rhGH therapy-are making it possible for PWS adults to live longer. Nevertheless, obesity-related comorbidities still remain the major contributors to morbidity and mortality in these patients, with the mortality rate reported up to 7% per year for those over 30 years of age [9]. Reduced intake of food containing vitamin D, less sunlight exposure, and scarce or absent physical activity (with preference given to indoor leisure activities) are all conditions that contribute to an increased risk of vitamin D deficiency in PWS adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations